2017
DOI: 10.1152/ajplung.00486.2016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane wounding and repair in pulmonary diseases

Abstract: Various pathophysiological conditions such as surfactant dysfunction, mechanical ventilation, inflammation, pathogen products, environmental exposures, and gastric acid aspiration stress lung cells, and the compromise of plasma membranes occurs as a result. The mechanisms necessary for cells to repair plasma membrane defects have been extensively investigated in the last two decades, and some of these key repair mechanisms are also shown to occur following lung cell injury. Because it was theorized that lung w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 284 publications
0
43
0
Order By: Relevance
“…In this regard it has been demonstrated in animal models that an isolated injury of AE2 cells or disruption of the surfactant system is either sufficient to induce a fibrotic lung remodeling (40,51,62,71,72) or results in a higher susceptibility for injury and fibrotic remodeling (69). Although the role of mechanical stress resulting from alveolar R/D and volutrauma is appreciated as an aggravating factor of lung injury in the context of ventilator-induced lung injury (11,50,63), the relevance for disease progression from acute lung injury to tissue remodeling and fibrosis during spontaneous breathing is less clear and therefore represents a gap of knowledge in the context of human diseases characterized by high surface tension, ongoing lung injury, and remodeling (20). In the present study we tested the hypothesis whether surfactant dysfunction is involved in aggravating/ triggering lung injury and remodeling processes such as collapse induration during the time course of disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard it has been demonstrated in animal models that an isolated injury of AE2 cells or disruption of the surfactant system is either sufficient to induce a fibrotic lung remodeling (40,51,62,71,72) or results in a higher susceptibility for injury and fibrotic remodeling (69). Although the role of mechanical stress resulting from alveolar R/D and volutrauma is appreciated as an aggravating factor of lung injury in the context of ventilator-induced lung injury (11,50,63), the relevance for disease progression from acute lung injury to tissue remodeling and fibrosis during spontaneous breathing is less clear and therefore represents a gap of knowledge in the context of human diseases characterized by high surface tension, ongoing lung injury, and remodeling (20). In the present study we tested the hypothesis whether surfactant dysfunction is involved in aggravating/ triggering lung injury and remodeling processes such as collapse induration during the time course of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, SRT modifies disease progression to collapse induration. surfactant; collapse induration; lung injury and fibrosis; stereology; bleomycin MECHANICAL STRESS is well accepted to contribute to the pathogenesis of acute lung injury in particular in the context of ventilator-induced lung injury where mechanical ventilation can aggravate preexisting early stages of lung injury (11,50). Harmful stresses operating on lung parenchyma result from atelectrauma and volutrauma (63).…”
mentioning
confidence: 99%
“… 28 TGF-β signaling plays vital roles in mediating pulmonary fibrosis when excessive repair appears. 29 Wang et al reported that multiwall carbon nanotubes could promote pulmonary fibrosis through TGF-β/Smad signaling pathway. 30 Our data showed that after being stimulated by a relatively higher dose of Dex (10 −4 M) for 48 hours, TGF-β was significantly higher compared with that in other groups.…”
Section: Discussionmentioning
confidence: 99%
“…While there are in-depth reviews of tissue level repair pathways [154,155], single cell plasma membrane repair has often been viewed as an event unrelated to tissue repair. In recent years the importance of plasma membrane repair in the pathophysiology of disease in many tissues has been appreciated [4,156]. It is also clear that overlapping mechanisms exist between the repair processes at the single cell and tissue scale [157].…”
Section: Shared Regulators Of Cellular and Tissue-level Repairmentioning
confidence: 99%